Parameter investigation of passive to semi active cooling technique for house in tropical climate - Norasmiza, Mohd (2023)
Malaysia's climate can be described as hot and humid throughout the year. Because of the extensive use of air conditioners to counter overheating, which contributes to global warming, energy consumption in residential buildings has become a major concern. Alternative methods, such as passive cooling, were explored as a solution to this issue. The usage of a double skin façade (DSF) as advanced feature that can reduce energy consumption and increase thermal comfort. To determine their effectiveness in lowering temperature, three parameters were considered. Within DSF, the number of inlets, number of gaps, and types of flow were investigated at the roof, wall, and floor. The experiment were conducted in indoor (controlled environment) and outdoor area. The indoor experiment was conducted in a test section where the ambient temperature was controlled. All model of house were placed inside the test section to analyze heat transfer rate and temperature in the house for heating and cooling mode. The test section was insulated by using polystyrene board and spray foam. One sensor was placed inside each of the house and 10 sensor were installed for test section. Two heater were used to heated up temperature above 50℃. A fan was turned on during cooling mode to induce flow. Next the experiment was conducted in spacious outdoor area by using actual weather mainly in Pekan, Pahang. The reading of temperature, velocity, humidity were recorded 10:00 am until 3:00 pm. Then, the significance of parameters was analyze by using Design of Experiment. One factor at time method was used to evaluate significance of parameter types of flow. Next three main parameter, number of inlet, number of gap and types of flow were validate their significance by using 2 level factorial design based on analysis of variance and pareto chart. Heat transfer rate was analyze using Fourier number and dimensionless temperature to determine best design heating and cooling mode. According to results show that the DSF leads to a reduction in indoor temperature. The house with 0 inlet and 3 gap had the lowest rate of heat transfer. Conduction in the heating mode was moderate increase in temperature. The optimum design for releasing heat and cooling the house by convection included house with 3 inlets and 3 gaps. The house with 3 inlets and 3 gaps was a major parameters. Maximum cooling rate was 15.12 ℃/h that contributed to the temperature difference over 10 ℃ with a minimum air velocity of 2m/s. Humidity difference that required to support the temperature difference was in range 14% to 20%. It was highly recommended that to design an eco house that apply passive to semi active cooling technique to reduce temperature in residential building. DSF was one of passive and semi active technique that have the ability of reduce temperature without using air conditioning system.